Analisis Determinasi Wilayah Kerja dan Pengoperasian Pelabuhan Perikanan Untia Makassar - Achmad Setiawan; Syamsul Hadi; Ghaffar, Mukhlisa A; Erna; Burhani, shidik; Andi Ana Humaerah; Herdy Pratama Putra (Jurnal Informasi, Sains dan Teknologi, 2025)
Determining the working and operational areas of a fishing port is very important because it strengthens the existence of a fishing port while supporting port operations. The purpose of this study is to determine the working and operational areas of the Untia fishing port based on the ratio of space utilization in land and water areas. The research method used is quantitative descriptive. Secondary data was obtained through literature surveys and institutional surveys to obtain port design plans and spatial planning plans, while primary data was obtained using satellite imagery and verified directly in the field to obtain geographical coordinates. Analysis was conducted on the position of the Untia port in relation to the provincial spatial planning plan, the physical condition, and the operational aspects of the port. The results obtained include the determination of geographical coordinates for the operational areas on land and water used for the construction and operation of main facilities, functional facilities, and supporting facilities for Untia fishing port. Based on the analysis results, the total operational area of the Untia Fisheries Port is determined to be 232.33 hectares, consisting of a land operational area of 9.8 hectares, a water operational area of 92.84 hectares, a land operational area of 23.56 hectares, and a water operational area of 106.13 hectares.